Enhancing Legal Awareness on Occupational Safety Crimes among SMK Students through IT-Based Educational Media for Pre-Employment Mitigation - Hamonangan Albariansyah; Mona Ervita; Ainun Jiwanti; Nadillah Maudi Cahyani (Majalah Ilmiah UPI YPTK, 2025)
This study presents the outcomes of a community service program aimed at strengthening the legal awareness of students at SMK Negeri 1 Indralaya Utara concerning occupational safety and health (OSH) crimes. The initiative utilized information technology–based educational media, including Canva-designed materials and a digital pocket book, as learning innovations to promote pre-employment legal literacy. A pre-test and post-test design measured students’ comprehension before and after counseling. Results showed a 4% improvement (47%–51%), indicating modest yet meaningful progress in understanding OSH laws and reporting procedures. Qualitative feedback revealed high engagement and improved awareness of legal mitigation practices. The program highlights that IT-assisted legal counseling effectively fosters preventive awareness among vocational students and serves as a replicable model for similar initiatives in other educational institutions.